Youth Employment Challenges and Skills Gap in Gulmi District, Nepal: An Analytical Study - Devkota, Chiranjivi (Chhahari छहारी, 2026)
Youth unemployment represents a profound and worsening challenge across developing countries, particularly within the Global South, with Nepal serving as a compelling case study of the comprehensive nature of the crisis. Despite a growing youth population, labor market integration remains weak due to persistent skills divergences, informal labor dominance, and structural limitations in employment policy and education. This study critically investigates the root causes of youth underemployment and joblessness in Dhurkot Rural Municipality of Gulmi District, Nepal through an analytical lens. It synthesizes national and international data sources, primary data-based survey, policy analyses, and academic literature to examine weaknesses such as the disconnect between educational outcomes and labor market demands, the predominance of informal employment, and the inefficacy of current institutional responses including Technical and Vocational Education and Training (TVET) programs and migration policies.The findings reveal that although government strategies such as the Prime Minister Employment Program (PMEP), Youth Vision 2025, and CTEVT-driven vocational training seek to address the problem, they are hindered by fragmentation, insufficient coordination with the private sector, lack of performance monitoring, and limited adaptability to labor market shifts. The paper recommends strengthening demand responsive skill development programs, creating strategic public-private partnerships, enhancing labor market information systems, and integrating career guidance within the educational curriculum. These insights offer a roadmap not only for Nepal but for similarly structured low- and lower-middle-income countries aiming to transform their youth expand into an engine of inclusive and sustainable growth.